1998
DOI: 10.1021/bi973072k
|View full text |Cite
|
Sign up to set email alerts
|

Anion Activation of 3-Phosphoglycerate Kinase Requires Domain Closure

Abstract: 3-Phosphoglycerate kinase is a typical two-domain "hinge-bending" enzyme, which is known to be regulated by multivalent anions. Here a relationship between this regulation and the hinge-bending domain closure is proposed on the basis of enzyme kinetic analysis and molecular modeling. Activation of the pig muscle enzyme at low concentrations and inhibition at high concentrations of various anionic analogues of the substrate 3-phosphoglycerate or of the nonsubstrate metal-free ATP are described by a two-site mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 57 publications
9
27
0
Order By: Relevance
“…Unlike the mesophilic PGK from yeast which shows a neutral pI (28) and an optimal pH for activity at pH 8.0, the pI of the psychrophilic enzyme is acidic, pI 4.9, and it is active over a broad pH range (6.5-10), with an optimal activity at pH 8.0 (data not shown). The cold-adapted enzyme is activated by sulfate ions at concentrations below 20 mM and is inhibited at concentrations above 50 mM, as already reported for mesophilic PGK (29,30). The first 15 amino acids of the N terminus were determined by Edman degradation and were found to be similar to that deduced from the gene sequence, displaying a removed formylmethionine and sharing substantial homology with other PGK sequences from different sources.…”
Section: Resultssupporting
confidence: 75%
“…Unlike the mesophilic PGK from yeast which shows a neutral pI (28) and an optimal pH for activity at pH 8.0, the pI of the psychrophilic enzyme is acidic, pI 4.9, and it is active over a broad pH range (6.5-10), with an optimal activity at pH 8.0 (data not shown). The cold-adapted enzyme is activated by sulfate ions at concentrations below 20 mM and is inhibited at concentrations above 50 mM, as already reported for mesophilic PGK (29,30). The first 15 amino acids of the N terminus were determined by Edman degradation and were found to be similar to that deduced from the gene sequence, displaying a removed formylmethionine and sharing substantial homology with other PGK sequences from different sources.…”
Section: Resultssupporting
confidence: 75%
“…The lack of ͚⌬H cal difference between the free and closed forms of PsPGK (TABLE ONE) also supports this view. Finally, in a thoughtful study of PGK activation, the authors concluded that it cannot be decided whether anion activation is a consequence of domain closure or anion binding itself mediates the closure by connecting the two domains (23). From our results, it seems that the latter hypothesis is valid, as demonstrated by the apparent domain closure induced by the sulfate anion activator (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…These results clearly demonstrate that the Mg 2ϩ -binding site belongs to the heat-stable DSC transition. Finally, the sulfate ion can be viewed as a test case for our assignment of the DSC transitions because it has been reported to bind both to the N-(Arg 61 ) and C-(Lys 192 ) domains (23). And indeed, increasing Na 2 SO 4 concentrations affect both the heat-labile and heat-stable DSC transitions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…has occurred as to whether 1,3-BPG and its analogs bind at more than one site on PGK (16), and it is now reasonably clear that at least in the open form it only has a single major binding site (13). Finally, by using a low concentration of both enzyme and CrADP along with tight binding PGK ligands we can ensure that essentially all of the paramagnetic relaxation of the ligand occurs while bound to the enzyme, and no significant relaxation occurs in a CrADP⅐ligand binary complex.…”
Section: Orientation Of 13-bpg Analogs Bound To Pgkmentioning
confidence: 99%
“…Another subject of intense study is the kinetics of the reaction, which is activated by anions (15). Although the issue has not been resolved, it is likely that an anion binding site is formed when the two domains close (16).…”
mentioning
confidence: 99%